Speech Function Used by the Characters in We're the Millers Movie - Mahutama, Nyoman Galang Adhiyaksa (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 1 (2024): Maret, 2024)
Abstract —This study aims to find the speech function category used by the characters in the movie entitled We’re the Millers and analyze the reason of the characters for using speech function category. In collecting data, this study used non-participant observation as a method and note taking as a technique. Descriptive qualitative was a method used to analyze the data. Then, the informal method was used as a method to present the results of the analysis to describe the speech function category used by the characters and the reason of the characters for using the speech function category in We’re the Millers movie. This study used the sociolinguistics theory proposed by Holmes (2013) about speech function category. The results of this study showed that the utterances that uttered by the characters in We’re the Millers movie contains all categories of speech function. Those categories were expressive, directive, referential, metalinguistic, poetic, and phatic. In addition, it was also found that the reasons of the characters for using the speech function categories were to express feeling, to give commands, to give information, to explain things, focuses on the aesthetic values on language, and to express empathy.